1999
DOI: 10.1126/science.285.5436.2122
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Fas Response and Autoimmunity in Pten +/− Mice

Abstract: Inactivating mutations in the PTEN tumor suppressor gene, encoding a phosphatase, occur in three related human autosomal dominant disorders characterized by tumor susceptibility. Here it is shown that Pten heterozygous (Pten+/-) mutants develop a lethal polyclonal autoimmune disorder with features reminiscent of those observed in Fas-deficient mutants. Fas-mediated apoptosis was impaired in Pten+/- mice, and T lymphocytes from these mice show reduced activation-induced cell death and increased proliferation up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
360
2
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 493 publications
(389 citation statements)
references
References 27 publications
25
360
2
2
Order By: Relevance
“…PTEN phosphatase antagonizes the activity of PI3K that phosphorylates Akt. It has been demonstrated that Fas-mediated apoptosis is impaired in PTEN-mutant mice, in which phosphorylation of Akt is abnormally elevated [21]. All things considered, our results suggest the possible involvement of PTEN, which increases in expression during terminal follicular development and luteinization, in the regulation of proliferation and differentiation of granulosa cells via regulation of Akt phosphorylation.…”
Section: Discussionsupporting
confidence: 58%
“…PTEN phosphatase antagonizes the activity of PI3K that phosphorylates Akt. It has been demonstrated that Fas-mediated apoptosis is impaired in PTEN-mutant mice, in which phosphorylation of Akt is abnormally elevated [21]. All things considered, our results suggest the possible involvement of PTEN, which increases in expression during terminal follicular development and luteinization, in the regulation of proliferation and differentiation of granulosa cells via regulation of Akt phosphorylation.…”
Section: Discussionsupporting
confidence: 58%
“…17 Subsequent studies in animal models have suggested that haploinsufficiency (i.e., loss of a single PTEN allele) alone may be sufficient for inducing protein loss and tumor progression. 32,33 Although definitive studies are lacking in breast cancer, that this may occur in humans is suggested by the fact that heterozygous inactivation of PTEN results in 3 dominantly inherited disorders: Cowden syndrome (associated with a predisposition to thyroid and breast cancers), Bannayan-Zonana syndrome and Lhermitte-Duclos syndrome. [3][4][5] Of course, this more likely suggests that it is easier to mutate the second allele once the first allele is lost.…”
Section: Resultsmentioning
confidence: 99%
“…While complete deletion of Pten results in embryonic lethality, [16][17][18] Pten +/À mice develop an autoimmune phenotype characterized by lymphadenopathy and splenomegaly that has been attributed to defective B-and T-cell apoptosis. 19 These mice also demonstrated autoimmunity, developing antibodies against nuclear antigens as well as immune complex-mediated glomerular disease. Immunopathology of Pten +/À mice was worsened when both alleles of Pten were deleted in the T-cell compartment.…”
Section: Introductionmentioning
confidence: 99%